Mechanisms controlling differential promoter-occupancy by the yeast forkhead proteins Fkh1p and Fkh2p: implications for regulating the cell cycle and differentiation - Hollenhorst, Peter C. (Cold Spring Harbor Laboratory Press, 2001)
The roles of DNA and Mcm1p interactions in determining the overlapping and distinct functions of the yeast cell cycle regulatory transcription factors Fkh1p and Fkh2p were examined. Full-length recombinant Fkh1p and Fkh2p were purified and their binding to bona fide promoters examined in vitro. Each protein bound a variety of target promoters with similar specificity in vitro, consistent with the observation that these proteins bind common promoters in vivo. However, in vivo, the Fkh1p and Fkh2p occupied different target promoters to different extents, suggesting that each was primarily responsible for controlling a different set of genes. Additional in vitro studies provided a mechanistic explanation for this differential promoter-occupancy. Specifically, the Fkh2p, but not the Fkh1p, was capable of binding cooperatively with Mcm1p. The Mcm1p–Fkh2p cooperative binding was enhanced by, but did not require, the presence of a Mcm1p-binding site within a target promoter. Consistent with these data, Mcm1p was present at Fkh-controlled promoters in vivo regardless of whether they contained Mcm1p-binding sites, suggesting a role for Mcm1p at promoters not thought previously to be under Mcm1p control. Analysis of Fkh1p and Fkh2p binding to promoter targets in vivo by use of mutant strains indicated that the two proteins compete for promoter-occupancy at a number of target promoters. We postulate that Fkh1p and a stable Fkh2p/Mcm1p complex compete for binding to target promoters and that the levels and/or binding activity of Fkh1p, but not Fkh2p, are most limiting for promoter-occupancy in vivo. Interestingly, the in vitro DNA-binding assays, using a variety of promoter targets, revealed that bona fide Fkh target promoters contained two or more Fkh-binding sites that allowed the Fkh1p and Fkh2p proteins to form multiple protein–DNA complexes in vitro. Multiple Fkh-binding sites may be a distinguishing feature of bona fide Fkh promoters in yeast and other organisms.